Structural design and economic analysis of prosthetic leg for below and above knee amputation. (2021) - Sundararaj, S.; Subramaniyan, G.V.
Abstract: Amputation is a surgical process of cutting off a limb and the amputees seek immediate replacement of prosthetic legs at an affordable cost. In this paper, the structural and economic analysis of below-knee (BK) and above-knee (AK) prosthetic leg using high-density polyethylene (HDPE), polyamide (PA) 6 or nylon 6, and polyamide (PA) 66 or nylon 66 materials with simulation software is carried out. The prosthetic leg with anatomical limb features such as the knee and ankle joints are analysed. The prosthetic legs are optimally designed to facilitate ease of manufacturing and to support varied loads imparted by the patient. The Von-Mises stress, equivalent elastic strain, and total deformation were obtained by considering loads for standing, walking, and running criteria. The analysis indicates that when polyamide is used as the base material, better structural performance is obtained in terms of strength compared to high-density polyethylene, while the latter facilitates reduced weight distribution with adequate strength properties.